Internalization of Spiritual Values in Shaping Students' Religious Character Through Religious Week Activities at SMA Negeri 1 Kartasura. - Dwi Suprapti; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
The aim of this research is to determine the extent of internalization of spiritual values in shaping students' religious character. This research uses a qualitative approach. The subjects of this research were teachers and students at SMAN 1 Kartasura. This research was carried out from October to December 2023 with the informants in this research namely the school principal, Islamic religious education teacher, and students. Meanwhile, data collection was carried out through observation, interviews and documentation. Data analysis was carried out using data reduction, data presentation and data verification. The results show that spiritual values are internalized through habituation before PAI lessons, Friday prayers and mentoring. Meanwhile, the supporting factors are habituated and religious week. The inhibiting factors are internal factors. Internal factors inhibiting the formation of students' religious character are age and psychological factors. External factors are under the influence of the family environment, school environment and of course the community environment.